Nafāqah as an Islamic Social Security Mechanism: Theoretical and Empirical Gaps in the Eastern Province of Sri Lanka - Saujan Iqbal; MIM. Jazeel; Yusuf Sani Abubakar (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
Nafāqah, the husband's obligation to provide maintenance to his wife in Islamic law, is a crucial social security mechanism in Islam's socio-economic system. Despite being regulated in classical texts, its implementation often faces significant gaps, especially in countries with Muslim minority populations. In the Eastern Province of Sri Lanka, nafāqah under the Muslim Marriage and Divorce Act No. 13 of 1951 (MMDA) shows institutional failure, influenced by post-conflict issues, the kudi system, and women’s economic roles. This article identifies gaps in nafāqah implementation in Sri Lanka, focusing on the failures of existing laws and the factors behind them. It proposes a conceptual framework for further research on nafāqah in this context. A systematic review of classical fiqh sources, comparative legal studies, and gray literature from Sri Lankan advocacy organizations reveals five key research gaps: lack of primary data, inadequate theoretical frameworks, unexplained relationships between women's employment and nafāqah, the kudi system’s impact on housing obligations, and the dominance of qualitative methods. The study highlights that institutional failures in implementing nafāqah in Eastern Sri Lanka are underexplored. The lack of primary data and inadequate theoretical frameworks hinder a deeper understanding of nafāqah practices. Further empirical research is essential to strengthen evidence regarding nafāqah’s role in fulfilling the rights of Muslim women. This article contributes by proposing a conceptual framework integrating Islamic fiqh and social science approaches and identifying data gaps that need further investigation. It also offers policy recommendations to support effective reforms of the MMDA to protect Muslim women’s rights in Sri Lanka.